Potentially inappropriate prescribing in hospitalized patients with comparative study between prescription by internits and geriatricians - A. J. Pardo-Cabello; S. Bermudo-Conde; V. Manzano-Gamero (Farmacia Hospitalaria, 2014)
Abstract: Objectives: To analyze potentially inappropriate prescribing in hospitalized patients and compare the prescription by internists and geriatricians. Methods: Cross-sectional study in hospitalized patients older than 65 years. We recorded prevalence of potentially inappropriate prescriptions according to the criteria of “Screening Tool of Older Person’s Prescriptions”. Results: We included 95 hospitalized patients over 65 years with a median age of 79 years (interquartile range: 73-82 years) and 50.5% female. One hundred eighty-three potentially inappropriate prescriptions were detected in 81 patients (85.2% of patients). The most frequent potentially inappropriate prescription were the prolonged use of inhibitors of proton pump high dose (32.6% of patients), the use of benzodiazepines in patients prone to falling (23.2% of patients), the prolonged use of long-acting benzodiazepines (21.1% of patients) and prolonged use of neuroleptic as hypnotics (21.1% of patients). In comparative study between medical specialties, significant differences were found in mean number of drugs (P = 0.0001) and in prolonged use of neuroleptics as hypnotics (P = 0.015). Conclusions: A high percentage of hospitalized patients older than 65 years receive potentially inappropriate prescribing. Prolonged use of inhibitors of the proton pump at high doses was the most frequent potentially inappropriate prescribing criterion.